1990
DOI: 10.1128/jb.172.2.741-747.1990
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the flagellar regulon of Salmonella typhimurium

Abstract: In Salmonella typhimurium, nearly 50 genes are involved in flagellar formation and function and constitute at least 13 different operons. In this study, we examined the transcriptional interaction among the flagellar operons by combined use of Mu dl(Apr Lac) cts62 and TnlO insertion mutants in the flagellar genes. The results showed that the flagellar operons can be divided into three classes: class I contains only theflhD operon, which is controlled by the cAMP-CAP complex and is required for expression of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
377
3
5

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(393 citation statements)
references
References 39 publications
8
377
3
5
Order By: Relevance
“…In addition, it also plays a central role in flagellum assembly, as it acts as a checkpoint for late motility gene transcription (2,14,30). In several bacterial species, including the spirochete T. denticola, inactivation of flgE results in a failure to complete flagellum filament synthesis (34,36,39,55). In the studies reported here, we found that inactivation of flgE resulted in cells that were nonmotile and deficient in PFs.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…In addition, it also plays a central role in flagellum assembly, as it acts as a checkpoint for late motility gene transcription (2,14,30). In several bacterial species, including the spirochete T. denticola, inactivation of flgE results in a failure to complete flagellum filament synthesis (34,36,39,55). In the studies reported here, we found that inactivation of flgE resulted in cells that were nonmotile and deficient in PFs.…”
Section: Discussionsupporting
confidence: 48%
“…4b) transcripts in SC-E1 were similar to those in the wild type. These results differ from those obtained for other bacteria, in which inhibition of hook protein synthesis results in the cessation of flagellin transcription (3,34,36). Thus, in B. burgdorferi, completion of the PF hook is not a checkpoint for transcriptional control of PF synthesis.…”
Section: Isolation Of the Sc-e1 Mutantcontrasting
confidence: 55%
See 2 more Smart Citations
“…These operons are divided into three classes according to their order of expression [7]. The master operon in the highest class governs the expression of the rest by activating operons in the second class.…”
Section: Introductionmentioning
confidence: 99%